Winston Churchill - John Perry (Mumbai, India Jaico, 2011)
Winston Churchill was querulous, childish, self-indulgent, and difficult. But he was also brilliant, tenacious, capable and one of the most influential men in history. This book gives a brilliant and narrative account of Churchill's astounding career that is unmatched in its shrewd insights and its unforgettable anecdotes. He captivated the world with his speeches and his writings. Born to an aristocratic family, young Winston was whisked off to boarding school at an early age and left in the care of a nanny, Elizabeth Everest. From a very young age, Churchill believed he was destined to play a great role in the life of his nation, and he determined to prepare himself. This book also covers Churchill's leadership during the war, especially at the outset, when England stood alone and in imminent danger of defeat.
Age Group: Adult
Keywords: Nonfiction; Biography; History